The influence of CaO addition on grain refinement of cast magnesium alloys. (15th March 2016) - Ali, Yahia; Qiu, Dong; Jiang, Bin; Pan, Fusheng; Zhang, Ming-Xing
Abstract: CaO was validated as an effective grain refiner for cast Mg alloys. 0.7 wt.% CaO addition led to significant reduction in grain size. As CaO particles were reproducibly found within the Mg grains, it was considered that CaO particles promoted heterogeneous nucleation. Additionally, some CaO particles were chemically reduced by Mg, which produced Ca solute and contributed to the grain refinement. The present work indicates that co-existence of active nucleants and solutes with high Q-values in the melt is essential to achieve the highest grain refining efficiency. For Mg alloys, chemical reactions should also be considered at inoculation treatment. Graphical abstract: